Vocational education and training in Romania : short description - (:unkn) unknown (Publications Office of the European Union, 2019)
This short description contributes to better understanding of vocational education and training (VET) in Romania by providing an insight into its main features and highlighting system developments and current challenges. It is published during the Romanian Presidency in the Council of the EU (first half of 2019). Romanian VET offers diverse paths for learners. It comprises professional and technological programmes, regularly updated to combat low participation in lifelong learning and early leaving from education and training. Recent system developments include the introduction of a dual VET form: it complements the work-based learning tradition in school-based programmes and aims at making VET a more attractive option for learners, while adapting training better to employer needs. (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; I 2.2.2 Osteuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungssteuerung; Bildungsfinanzierung; Bildungspersonal; Rumänien